Assessing the role and capacity of water management organisations for ensuring delta food security in Bangladesh - Nath, D.K.; Mondal, M.K.; Mojid, M.A.; Jayasiri, M.M.J.G.C.N.; Jagadish, S.V.K.; Yadav, S. (TU Delft, 2024)
The coastal zone, consisting of one-third country's area, is the most climate-vulnerable region of Bangladesh. The country has invested significantly in coastal zone through the construction and rehabilitation of polders. Despite vast opportunities, land productivity in the polders is very low due to poor water governance and management. To improve in-polder water management, the responsibility of operation and maintenance of the polder water infrastructure has been transferred to Water Management Organizations (WMOs) since 2001. WMOs are currently voluntary organizations but are very important for micro-level agricultural water management. A study was conducted in 2017 and 2018 in a medium saline polder; with a major focus on organizational behaviour: hierarchy in decision-making, transparency, financial accountability, leadership, internal communication, and motivational incentives of the WMOs. The data were collected through a structured questionnaire from 192 respondents of randomly selected eight Water Management Groups (WMGs – the lowest tier of WMOs), out of 40 WMGs of the polder. The results revealed that the WMGs operations are not fully participatory in principle yet. Even the transparency, financial accountability, leadership, and internal communications within WMGs are not strong enough to take the organizational responsibility to address future challenges in food security of the climate-vulnerable polder communities. Improving drainage through efficient water management showed a yield gain of at least 1.5 t/ha in the wet season only. In addition, improved drainage fosters sustainable year-round cropping with high-yielding, high-value and nutrition-rich crops with 2 to 3 times higher productivity than the traditional cropping system. Therefore, investment in water governance particularly in improving drainage in the polders could be a major game-changer in sustaining the food security of the climate-vulnerable polder communities of Bangladesh. The study identified the knowledge gap as a significant concern that demands the need for capacity building of the WMOs.